Hallucination-Specific structure-function associations in schizophrenia. (30th November 2020) - Roes, Meighen M.; Yin, John; Taylor, Laura; Metzak, Paul D.; Lavigne, Katie M.; Chinchani, Abhijit; Tipper, Christine M.; Woodward, Todd S.
Highlights: Frontotemporal thinning linked with language network hyperactivity in hallucinators. Hallucinators' language network hyperactivity specific to passive speech perception. Multimodal CPCA revealed structure-function associations related to hallucinations. Abstract: Combining structural (sMRI) and functional magnetic resonance imaging (fMRI) data in schizophrenia patients with and without auditory hallucinations (9 SZ_AVH, 12 SZ_nAVH), 18 patients with bipolar disorder, and 22 healthy controls, we examined whether cortical thinning was associated with abnormal activity in functional brain networks associated with auditory hallucinations. Language-task fMRI data were combined with mean cortical thickness values from 148 brain regions in a constrained principal component analysis (CPCA) to identify brain structure-function associations predictable from group differences. Two components emerged from the multimodal analysis. The "AVH component" highlighted an association of frontotemporal and cingulate thinning with altered brain activity characteristic of hallucinations among patients with AVH. In contrast, the "Bipolar component" distinguished bipolar patients from healthy controls and linked increased activity in the language network with cortical thinning in the left occipital-temporal lobe. Our findings add to a body of evidence of the biological underpinnings of hallucinations and illustrate a method for multimodal data analysis of structure-function associations in psychiatric illness.